DEPRESSION IN CANCER PATIENTS DURING COVID-19 PANDEMIC. - Otroshchenko , Petr; Otroshchenko, Natalia; Iryna, Otroshchenko (The Ukrainian Scientific Medical Youth Journal, 2021)
More than 100 million confirmed accidents and more than 2 million deaths - this is the summary of СOVID-19 in mid-2021 when the whole world is experiencing the worst twilight of the pandemic. At the same time, the WHO European Regional Office considers this period to be the tipping point of the pandemic, linking it to the beginning of mass vaccination and the accumulated experience in the diagnosis and treatment of COVID-19 and its consequences, Despite the emergence of new mutations of the virus, the presence of prolonged forms of the disease (long-COVID, or post-COVID syndrome) (World Health Organization. Statement by Dr. Hans Henri P. Kluge, WHO Regional Director for Europe. Copenhagen, 7 January 2021). Apart from psychotic disorders of infectious origin in СOVID-19 (mental confusion, psychomotor agitation, delirious, hallucinatory, beacon-like, and affective disorders), non-productive changes in consciousness may develop, post-traumatic stress disorder (PTSD), non-psychotic asthenic states, depression, hypochondriacally disorders, sleep disorders, autonomic manifestations, cognitive deficit disorder, secondary encephalopathy, organ disorders (Kumar S., et al., 2021; Einvik G, et al., 2021). The prevalence of infectious psychosis has a pronounced tendency to decrease, while non-psychotic and cognitive deficit disorders after COVID-19 occur more frequently (Hampshire A., et al., 2020). At this time, the rate of depression and anxiety disorders due to the influence of coronavirus infection is significantly higher than in previous years (McCracken L.M., et al., 2020; Kujawa A., et al., 2020). Among the predictors of their development under pandemic conditions are COVID-19 symptoms, history of somatic disorders, oncological diseases, interim measures, and financial losses. A major stressor effect of the COVID-19 pandemic can provokenosocomial depression in COVID-19 postinfectious cancer patients, a complication in the course of postinfectious depression, and an exacerbation of depression in patients with an infectious disorder in their medical history (Petelin D.S, 2018; Dorozhenok I.Yu., 2021). Depression invariably attracts the attention of physicians. The main reasons for this are its widespread and widespread manifestations and variants of disorder that affect a significant number of people of different stature, age, social groups, and cultures. Women suffer from depression more often than men. According to the World Health Organization, more than 350 million people in the world suffer from depression (World Health Organization.Depression., 2018). The prevalence of depression in cancer is significantly higher than in the general population and, according to physicians, ranges from 33 to 42% (Otroshchenko N. P., et al., 2019). Symptoms of depression are diagnosed in every fourth oncologic patient and occur more frequently in the later stages of the disease. Unfortunately, these patients do not often come into the psychiatrist’s field of vision, because, considering the specifics of the disease, they are under the care of oncologists, and they turn to psychiatrists only in cases of major depression or suicidal attempts. High rates of depression (23%) are diagnosed with the most common forms of gynecologic cancer, cervical cancer, and uterine cancer (Arnaboldy P., et al., 2016; Bulletin of the National Cancer Registry N 20 - Cancer in Ukraine, 2017-2018; Petelin D.S., 2018; Otroshchenko N. P., et al., 2019). Comorbidity of oncologic diseases and coronavirus disease causes the risk of serious complications of these viral infections and requires the development and implementation of medical, social, and other protection measures for cancer patients, as well as for patients who have had cancer or other diseases and diseases that impair the function of the immune system (Tian, Y., et al., 2021). Therefore, the relevance of the study of post-covid depression (Hampshire A., et al., 2020; Kumar S., et al., 2021), including in patients with cancer (Tian, Y., et al, 2021), is due to the significant number of cervical and uterine cancerpatients, comorbidity, lack of early effective diagnosis, psychological and psychiatric support, late call for help, the tendency to chronicity, and risk of self-harm (Arnaboldy P., et al., 2016; Petelin D.S., 2018; Otroshchenko N. P., et al., 2019).